The effect of grinding and roasting conditions on the selective leaching of Nd and Dy from NdFeB magnet scraps - Yoon, H.; Kim, C.; Chung, K.; Jeon, S.; Park, I.; Yoo, Kyoungkeun; Jha, M. (MDPI AG, 2015)
The pretreatment processes consisting of grinding followed by roasting were investigated to improve the selective leaching of Nd and Dy from neodymium-iron-boron (NdFeB) magnet scraps. The peaks of Nd(OH)3 and Fe were observed in XRD results after grinding with NaOH as the amount of water addition increased to 5 cm3. These results indicate that the components of Nd and Fe in NdFeB magnet could be changed successfully into Nd(OH)3 and Fe, respectively. In the roasting tests using the ground product, with increasing roasting temperature to 500 °C, the peaks of Nd(OH)3 and Fe disappeared while those of Nd2O3 and Fe2O3 were shown. The peaks of NdFeO3 in the sample roasted at 600 °C were observed in the XRD pattern. Consequently, 94.2%, 93.1%, 1.0% of Nd, Dy, Fe were leached at 400 rpm and 90 °C in 1 kmol·m−3 acetic acid solution with 1% pulp density using a sample prepared under the following conditions: 15 in stoichiometric molar ratio of NaOH:Nd, 550 rpm in rotational grinding speed, 5 cm3 in water addition, 30 min in grinding time, 400 °C and 2 h in roasting temperature and time. The results indicate that the selective leaching of Nd and Dy from NdFeB magnet could be achieved successfully by grinding and then roasting treatments.